LINGUOCULTURAL SPECIFICITY OF EMOTION VERBALIZATION: A COMPARATIVE STUDY OF ENGLISH AND UZBEK IDIOMATIC EXPRESSIONS - Yusupova Fotima Alisher kizi, (TADQIQOTLAR, 2026)
Abstract:  This  article  examines  the  linguocultural  specificity  of  emotion verbalization  through  a  comparative  analysis  of  English  and  Uzbek  idiomatic expressions. Idioms serve as important linguistic tools for expressing emotions and reflect the cultural values, beliefs, and cognitive patterns of a speech community. The study explores similarities and differences in the representation of emotions such as happiness, sadness, anger, fear, and love in English and Uzbek idioms. The findings reveal that while some emotional concepts are universal, their linguistic realization is strongly influenced by cultural and historical factors. The research contributes to the fields of linguoculturology, cognitive linguistics, and cross-cultural communication.